Implications of hospital accreditation on the everyday lives of healthcare professionals - Manzo, Bruna Figueiredo; Brito, Maria José Menezes; Corrêa, Allana dos Reis (Revista da Escola de Enfermagem da USP, 2012)
Hospital accreditation processes should be adopted to achieve the highest standards of healthcare. This process requires behavioral changes and mobilization of professionals in efforts to achieve goals and objectives, in addition to continuous improvement of healthcare. This qualitative case study was performed with the objective of analyzing the implications of hospital accreditation on the everyday lives of healthcare workers in a private hospital in Belo Horizonte. Subjects were 34 healthcare professionals from different sectors of the hospital. Data were collected through semi-structured interviews and subjected to content analysis. It was observed that the accreditation process was designed as an opportunity for developing and improving the critical thinking capacity of the subjects involved. However, the requirements imposed by this process may trigger occupational stress and cause work overload.